Baseline sensitivities of three fungal pathogens of citrus to strobilurin fungicide and difenoconazole - HOU Xin; CHEN Guoqing; WANG Xinghong; ZHU Li; LI Hongye (浙江大学学报. 农业与生命科学版, 2013)
Melanose (Diaporthe citri), black spot (Guignardia citricarpa) and greasy spot (Mycospharella citri) of citrus have been becoming more and more serious and widespread, causing significant losses to the Chinese citrus industry by reducing yield and fruit quality in recent years. Although the improvement of cultural practices has the positive effect, application of fungicides is still the primary and effective means to control these diseases. Difenoconazole (belong to 14α-demethlylation inhibitors, DMIs) is a fungicide recently registered for use on citrus in China. ZJ0712 (belong to strobilurin, Qol), developed independently by our country, has a high potential in controlling citrus fungal diseases. The objective of this study was to establish the baseline sensitivity of these citrus fungal pathogens to these fungicides prior to their widespread use.Forty-eight single-spore strains of D. citri, 46 strains of G. citricarpa and 50 strains of M. citri were collected from main citrus-producing regions in China. The effective dose to reduce mycelial growth or spore germination by 50%(EC50 values) of each strain was determined by using eight different concentrations of fungicides. The results demonstrated that the baseline sensitivities for mycelial growth of D. citri, G. citricarpa and M. citri to ZJ0712 were 0.003,0.011 and 0.035 μg/mL, respectively; to difenoconazole were 0.149, 0.008 and 0.970 μg/mL, respectively. The baseline sensitivities for conidial germination of D. citri to ZJ0712 was 0.001 μg/mL, but> 25 μg/mL to difenoconazole.These results above indicated that the populations of D. citri, G. citricarpa and M. citri were sensitive to ZJ0712, and the populations of G. citricarpa and M. citri were sensitive to difenoconazole, implying widely potential usage of these fungicides in controlling the diseases above. Determination of the baseline sensitivities of D. citri, G. citricarpa and M. citri should also facilitate the detection and verification of pathogen resistance development to ZJ0712 and difenoconazole.